ANALISIS KINERJA KODE BCH DAN WALSH DALAM SISTEM DIRECT SEQUENCE SPREAD SPECTRUM PADA KANAL FREQUENCY SELECTIVE FADING - Joa Quin; Nyoman Pramaita; I Gst A. Komang Diafari Djuni H (Jurnal SPEKTRUM, 2025)
This research aims to analyze the performance of Bose–Chaudhuri–Hocquenghem (BCH) (7,4) coding in a Direct Sequence Spread Spectrum (DSSS) system using Walsh spreading codes under selective fading and Additive White Gaussian Noise (AWGN) channels. The simulation was conducted using MATLAB Simulink by varying the energy-per-bit to noise power spectral density ratio (Eb/No) to evaluate system performance based on the Bit Error Rate (BER). The results show that applying BCH(7,4) significantly reduces the BER, especially at moderate to high Eb/No levels. Furthermore, the combination of Walsh codes with BCH(7,4) demonstrates superior performance compared to systems without error correction. This study highlights the importance of proper selection of spreading and error correction methods in optimizing digital communication performance over multipath fading channels.